-(3x-3)-(10x-6)+8=-4(x-1)-(14x+5)+3

Simple and best practice solution for -(3x-3)-(10x-6)+8=-4(x-1)-(14x+5)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(3x-3)-(10x-6)+8=-4(x-1)-(14x+5)+3 equation:


Simplifying
-1(3x + -3) + -1(10x + -6) + 8 = -4(x + -1) + -1(14x + 5) + 3

Reorder the terms:
-1(-3 + 3x) + -1(10x + -6) + 8 = -4(x + -1) + -1(14x + 5) + 3
(-3 * -1 + 3x * -1) + -1(10x + -6) + 8 = -4(x + -1) + -1(14x + 5) + 3
(3 + -3x) + -1(10x + -6) + 8 = -4(x + -1) + -1(14x + 5) + 3

Reorder the terms:
3 + -3x + -1(-6 + 10x) + 8 = -4(x + -1) + -1(14x + 5) + 3
3 + -3x + (-6 * -1 + 10x * -1) + 8 = -4(x + -1) + -1(14x + 5) + 3
3 + -3x + (6 + -10x) + 8 = -4(x + -1) + -1(14x + 5) + 3

Reorder the terms:
3 + 6 + 8 + -3x + -10x = -4(x + -1) + -1(14x + 5) + 3

Combine like terms: 3 + 6 = 9
9 + 8 + -3x + -10x = -4(x + -1) + -1(14x + 5) + 3

Combine like terms: 9 + 8 = 17
17 + -3x + -10x = -4(x + -1) + -1(14x + 5) + 3

Combine like terms: -3x + -10x = -13x
17 + -13x = -4(x + -1) + -1(14x + 5) + 3

Reorder the terms:
17 + -13x = -4(-1 + x) + -1(14x + 5) + 3
17 + -13x = (-1 * -4 + x * -4) + -1(14x + 5) + 3
17 + -13x = (4 + -4x) + -1(14x + 5) + 3

Reorder the terms:
17 + -13x = 4 + -4x + -1(5 + 14x) + 3
17 + -13x = 4 + -4x + (5 * -1 + 14x * -1) + 3
17 + -13x = 4 + -4x + (-5 + -14x) + 3

Reorder the terms:
17 + -13x = 4 + -5 + 3 + -4x + -14x

Combine like terms: 4 + -5 = -1
17 + -13x = -1 + 3 + -4x + -14x

Combine like terms: -1 + 3 = 2
17 + -13x = 2 + -4x + -14x

Combine like terms: -4x + -14x = -18x
17 + -13x = 2 + -18x

Solving
17 + -13x = 2 + -18x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18x' to each side of the equation.
17 + -13x + 18x = 2 + -18x + 18x

Combine like terms: -13x + 18x = 5x
17 + 5x = 2 + -18x + 18x

Combine like terms: -18x + 18x = 0
17 + 5x = 2 + 0
17 + 5x = 2

Add '-17' to each side of the equation.
17 + -17 + 5x = 2 + -17

Combine like terms: 17 + -17 = 0
0 + 5x = 2 + -17
5x = 2 + -17

Combine like terms: 2 + -17 = -15
5x = -15

Divide each side by '5'.
x = -3

Simplifying
x = -3

See similar equations:

| 9=-7+1-6 | | -y-5=-9 | | 5(x-8)+x=6(x-8)+8 | | 11x+29y=-13 | | n+7n/5=72 | | 5x+15-4x=-6-12 | | 3/x=13/5x+2 | | 15w^3+14w^2-8w=0 | | -18-6k=6(1+2k) | | 17x=16x-24 | | 7(2x+3)=7 | | 5y+2(y-2)=7y-2(y-10) | | 17x=16x | | x/12=x/4-2 | | E=lR | | 44=-u+188 | | 18x+64=19x | | x/5=x/6-3 | | 0x^2-71x-9=0 | | 106=161-w | | 4x^2-13x+3x=0 | | (15/x)=((x^2)-7x+17) | | -v+111=202 | | 1/3+7/8+4/5 | | -x+279=208 | | 3x-6(x+1)=-3x+19 | | 21/5(-13/4p+5)=651/5 | | X(6x-3)=(6x+9)(x-8) | | -4(5y-7)-y=-2(y-5) | | x*y=630 | | x(2x+3)=4 | | 3(x-8)=9x |

Equations solver categories